Allegory in the fiction of Janet Frame : a thesis in partial fulfilment of the requirements for the degree of Doctor of Philosophy in English at Massey University - Panny, Judith Dell (Massey University, 1991)
This investigation considers some aspects of Janet Frame's fiction that have hitherto remained obscure. The study includes the eleven novels and the extended story "Snowman, Snowman". Answers to questions raised by the texts have been found within the works themselves by examining the significance of reiterated and contrasting motifs, and by exploring the most literal as well as the figurative meanings of the language. The study will disclose the deliberate patterning of Frame's work. It will be found that nine of the innovative and cryptic fictions are allegories. They belong within a genre that has emerged with fresh vigour in the second half of this century. All twelve works include allegorical features. Allegory provides access to much of Frame's irony, to hidden pathos and humour, and to some of the most significant questions raised by her work. By exposing the inhumanity of our age, Frame prompts questioning and reassessment of the goals and values of a materialist culture. Like all writers of allegory, she focuses upon the magic of language as the bearer of truth as well as the vehicle of deception. She shows that language, in transferring culture and custom from generation to generation, is an instrument of immense power; it may create and preserve, or it may instigate destruction.
Keywords: Janet Frame; Allegory; Frame, Janet